Olfactory-based Augmented Reality Support for Industrial Maintenance - ahmet Erkoyuncu, John (Cranfield University, 2020)
Augmented reality (AR) applications have opened innovative ways for performance improvement in the IoT industry. It can enhance user perception of the real-world by providing valuable information about an industrial environment and provide visual virtual information onto a head-mounted device (HMD). Such information is important for maintainers to quickly detect abnormalities, reduce nugatory routinesand facilitate preventive maintenance activities. Since odors are made up of volatile compounds at low concentration, they can be used for olfactory-based identification. The article outlines the development an olfactory-based AR system to help with the identification of maintenance issues using smell. The prototype comprises of three components: an electronic nose, a database and an AR application integrated with Microsoft HoloLens. After diagnosing an odor, the data is sent wirelessly through a local network to the HMD worn by the user. To validate the technology, four odors have been used, including engine oil, sun lotion, medical alcohol and perfume, to record behaviors and demonstrate the repeatability of the process. The presented technology incorporates sampling methods, cleaning processes and statistical analysis that can be further scrutinized to allow better smell augmentation for diagnosis.
Keywords: 'smell identification task'; 'Augmented Reality,'; 'Computer Engineering'; 'Control Systems; Robotics and Automation'